Dehydration of Ethanol Using Pervaporation Separation with Nanoporous Hydrophilic Silica Ceramic Membrane - Al-Mayah, Ameel Mohammed Rahman; Zair, Zyad Rafaa; Al-Hassani, Maha Hadi (Al-Khwarizmi Engineering Journal, 2012)
The pervaporation using a commercial hydrophilic ceramic membrane supplied from PERVATECH was conducted. The dehydration of ethanol/ water system was used as a model for the pervaporation study. Pervaporation experiments of ethanol/water system were carried out in the temperature range of 303-343K, ethanol concentration in the feed 10-90 vol. % and the feed flow rate in the range of 0.5-10 L/min. In this work, the effect of operation parameters on permeates fluxes as well as permeates separation factors have been studied. The Water flux is strongly dependent on the temperature; it increased with increasing in temperature, which in turn decreased the selectivity of membrane to water molecules. In addition water flux was decreased with increasing of ethanol concentration and increased with increasing feed flow rate. The optimal operational conditions of pervaporation process are: T=333 K, feed flow rate 6 L/min, and 90 vol.% ethanol concentration in the feed. High values of water flux and separation factor were obtained. The final results agreed well with other studies reported in the literature.